2003
DOI: 10.1088/0031-9155/48/12/307
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation on intra-fractional organ motion effects in lung IMRT treatments

Abstract: Respiration-induced tumour motion can potentially compromise the use of intensity-modulated radiotherapy (IMRT) as a dose escalation tool for lung tumour treatment. We have experimentally investigated the intra-fractional organ motion effects in lung IMRT treatments delivered by multi-leaf collimator (MLC). An in-house made motor-driven platform, which moves sinusoidally with an amplitude of 1 cm and a period of 4 s, was used to mimic tumour motion. Tumour motion was simulated along cranial-caudal direction wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
219
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(239 citation statements)
references
References 12 publications
13
219
1
2
Order By: Relevance
“…This is due to the canceling out of hot/cold spots when many fractions are combined. These results compare favorably with a previous experiment performed using an ion chamber for measurement (7) . In that study, the standard deviation was 0.19% and 0.35% for two different patients for 30 fractions.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This is due to the canceling out of hot/cold spots when many fractions are combined. These results compare favorably with a previous experiment performed using an ion chamber for measurement (7) . In that study, the standard deviation was 0.19% and 0.35% for two different patients for 30 fractions.…”
Section: Resultssupporting
confidence: 87%
“…The motion of the platform was set in the S‐I direction and the MLC leaves moving across the patient such that the two motions were always perpendicular. This was done to ensure consistency with a previously published study (7) . As a control, each of the five fields was measured individually, as well as a single film containing all five fields, with the platform in a static state.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors40, 41 have shown that extreme dose variations of up to 100% in IMRT field delivery due to the interplay effect are theoretically possible. Subsequent statistical analysis by Bortfeld42 found no significant difference over long course treatments (>10 fractions) however, comparisons were made against an introduced formalism rather than a CT dose distribution (of which variations of up to 20% were noted).…”
Section: Introductionmentioning
confidence: 99%